Law, person, and community philosophical, theological, and comparative perspectives on canon law - Coughlin, John J., 1954- (New York ; Oxford : Oxford University Press, 2012)
This publication takes up the fundamental question 'What is law?' through a comparative study of canon law and secular legal theory. The book also includes comparative consideration of the failure of canon law to address the clergy sexual abuse crisis the canon law of marriage, administrative law, the rule of law and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Canon law -- Social aspects; Canon law -- History; Catholics -- Legal status, laws, etc. -- United States